DESAIN MODUL MATEMATIKA BILINGUAL (INDONESIA-ARAB): PENGEMBANGAN MODUL KOMPETISI SAINS MADRASAH (KSM) MATEMATIKA TERINTEGRASI - Susanti, Nawal Ika; Insaniyah, Anyes Lathifatul (Department of Mathematics Education , University of Jember, 2023)
This research aims to develop a bilingual mathematics module for KSM in the field of integrated mathematics. The research method uses the Research and Development (RnD) method of the Borg and Gall model which is simplified in 4 stages, namely introduction, development, testing and dissemination. The results of the development of a bilingual (Indonesian-Arabic) mathematics module at KSM are suitable for use. The validation results from media experts have an average value of 3.69 and are in the suitable category for use. Media expert validation has an average value of 3.70 and is in the category suitable for use. The validation results by practitioners have an average value of 3.62 and are in the suitable category for use. Trials by subject teachers had an average score of 3.71 and were in the very interesting category. The individual trials had an average score of 3.61 and were in the very interesting category. Small group trials in each madrasah had an average score of 3.83 and were in the very interesting category and large group trials had an average score of 3.74 and were in the very interesting category. The final stage is dissemination carried out by distributing bilingual mathematics module books.